Heritability of metabolic syndrome traits among healthy younger adults: a population based study in China. Issue 6 (15th September 2009) - Luo, B F; Du, L; Li, J X; Pan, B Y; Xu, J M; Chen, J; Yin, X Y; Ren, YQ; Zhang, F
Abstract : Objective: To estimate heritability of metabolic syndrome traits among healthy younger adults in a human population in China, and examine potential sex differences in heritability and parental effect on metabolic syndrome traits. Methods: Using offspring–parent regression, we estimated heritability (h 2 ) of metabolic syndrome traits based on 452 child–parent triads identified from a population based random survey on metabolic syndrome among people over 15 years of age in Guangzhou, China. Results: Body mass index (BMI), cholesterol, high density lipoprotein cholesterol (HDL-C), low density lipoprotein cholesterol (LDL-C), fasting plasma glucose (FPG) and waist circumference (waist-C) were more heritable (h 2, 0.42–0.545), whereas systolic blood pressure (SBP), diastolic blood pressure (DBP), and triglycerides (TG) were less heritable (h 2, 0.14–0.28). Sons had pronounced increases in heritability for all traits over daughters, particularly for cholesterol (0.653 vs 0.356), FPG (0.602 vs 0.313), LDL-C (0.521 vs 0.329), and TG (0.395 vs 0.187). Offspring–mother seemed to have a higher heritability in every trait except FPG (0.67 vs 0.794) than offspring–father, most notably for DBP (0.308 vs 0.122), SBP (0.288 vs 0.146), TG (0.387 vs 0.239) and waist-C (0.581 vs 0.354). Conclusion: We estimated the heritability of metabolic syndrome traits in a human population based on a unique population based offspring–parent sample from China, and found important evidence that the maternal and paternal effects on these traits are different and the sex difference in heritability is pronounced.